Building ecotheological awareness through the Gontor Islamic song “Akankah Dunia Rela”: An analysis of educational values in the lyrics - Lhegina, Assyifa Qori; Muqowim; Maulaya, Rosendah Dwi; Hamami, Tasman (Tawazun: Jurnal Pendidikan Islam, 2026)
The escalating global ecological crisis indicates that environmental problems are not merely technical issues, but are closely related to moral, ethical, and spiritual dimensions. In Islamic education, the development of students’ ecological awareness therefore needs to be integrated with theological perspectives to foster transformative and sustainable attitudes. This study aims to analyze the ecotheological values embedded in the lyrics of the song Akankah Dunia Rela and to examine their relevance as a learning medium in Islamic Religious Education (PAI) for building students’ ecotheological awareness. The research employs a qualitative approach using interpretative-critical content analysis. The primary data source is the lyrics of Akankah Dunia Rela KH Hsan Abdullah Sahal, a Kiai from Gontor,, supported by scholarly literature on Islamic ecotheology, environmentally oriented Islamic education, and the use of songs as educational media. The findings indicate that the song contains key Islamic ecotheological values, including ecological monotheism (tauhid ekologis), human stewardship (khalifah), the prohibition of environmental destruction (fasad fil ardh), moral responsibility, social and environmental care, spiritual reflection, and ecological advocacy. These values reflect an ethical relationship between God, humanity, and nature, and are highly relevant for integration into PAI learning. This study concludes that religious songs can serve as reflective and pedagogical media to cultivate students’ ecological-spiritual awareness. Theoretically, this research contributes to the development of Islamic ecotheology in the cultural sphere, while practically offering a contextual and transformative learning medium for Islamic education. Abstrak Krisis ekologi global yang semakin meningkat menunjukkan bahwa permasalahan lingkungan tidak semata-mata bersifat teknis, tetapi berkaitan erat dengan dimensi moral, etika, dan spiritual. Dalam konteks pendidikan Islam, pengembangan kesadaran ekologis peserta didik perlu diintegrasikan dengan perspektif teologis guna membentuk sikap yang transformatif dan berkelanjutan. Penelitian ini bertujuan untuk menganalisis nilai-nilai ekoteologis yang terkandung dalam lirik lagu Akankah Dunia Rela yang dirilis oleh KH. Hasan Abdullah Sahal yang merupakan Kiai Gontor serta mengkaji relevansinya sebagai media pembelajaran Pendidikan Agama Islam (PAI) dalam membangun kesadaran ekoteologis peserta didik. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis isi interpretatif-kritis. Sumber data utama berupa lirik lagu Akankah Dunia Rela yang didukung oleh literatur ilmiah terkait ekoteologi Islam, pendidikan Islam berwawasan lingkungan, serta pemanfaatan lagu sebagai media pembelajaran. Hasil penelitian menunjukkan bahwa lagu tersebut memuat nilai-nilai ekoteologi Islam yang signifikan, meliputi tauhid ekologis, peran manusia sebagai khalifah, larangan perusakan lingkungan (fasad fil ardh), tanggung jawab moral, kepedulian sosial dan lingkungan, refleksi spiritual, serta advokasi ekologis. Nilai-nilai tersebut merefleksikan hubungan etis antara Tuhan, manusia, dan alam, serta relevan untuk diintegrasikan dalam pembelajaran PAI. Penelitian ini menegaskan bahwa lagu religius dapat berfungsi sebagai media reflektif dan pedagogis dalam menumbuhkan kesadaran ekologis-spiritual peserta didik, sekaligus memperkaya pengembangan ekoteologi Islam dalam ranah budaya dan praktik pendidikan.